The Effectiveness of Contextual Teaching and Learning Method to Improve Students’ Speaking Skills at the First Grade Students of SMPN 12 Langgudu Satap - Rohana, Putri; Suratman, Suratman; Annisah, Annisah (FKIP - Universitas Riau, 2025)
Implementation of contextual teaching and learning (CTL) method need to be assessed. This research aims to determine the effectiveness of the CTL method to improve students’ speaking skills. It was conducted at SMPN 12 Langgudu Satap with a total of 13 students, 9 female and 4 male students. This research method used quantitative approach with a pre-experimental one group pretest-posttest design. The data was obtained by compare students’ speaking test results before and after treatment in the same group without a control group. The results showed that applying the CTL method was effective in improving students’ speaking skills. Students were able to speak more clearly, confidently and explain objects in more detail. There is a positive change from the pretest average score of 46.15, which increased to 69.23 in the posttest. Moreover, the paired sample t- test conducted using SPSS shows a significance value of 0.000 <0.05. Based on the decision making guideline, H0 is rejected and Ha is accepted if the significance value (sig.2-tailed) < 0.05. Therefore, it can be concluded that CTL method effectively to improve students’ speaking skills at the first grade students of SMPN 12 Langgudu Satap.